(untitled) (Revista Española de Fisiología, 1990)
In the present work the label of L-T3 and L-T4 with RBITC have been developed by means of a relatively easy procedure. A purification by TLC, previously optimized, offers the possibility of obtaining a good recovery of conjugates T3 and T4-RBITC. The immunoreactivity of conjugates was calculated by a formulas especially designed for this purpose. This formulas could be applied to any molecule labelled with fluorescent compounds.